Occurrence of severe cognitive impairment in elderly individuals with poor glycemic control Vs elderly individuals with good glycemic control or no DM: a case control study” - Salman, Basma; Jehangir, Fatima; Jahan, Aroosa; Aslam, Saira; Ansari, Nadra (Journal of Rawalpindi Medical College, 2023)
ABSTRACT: Background: There is substantiatial corroboration that diabetes (both T1DM and T2DM) plays an essential role in predisposition to cognitive decline thus leading to dementia in both human and animal studies. (1,2,3). Hypoglycemia has been associated with the increased risk of developing cognitive impairment. (4). There is lack of data from our community to support this. We aim to observe occurrence of cognitive impairment in individuals aged 65 or above with poor glycemic control and compare it with similar age group individuals with no DM or good glycemic control. Frailty independently contributes to the cognitive decline. We also assessed frailty index and incorporated it into our result interpretation. Methods: We conducted a case control study in the primary health care center of Ziauddin University from 1st December 2021 to 30th June 2022. Cases included 83 individuals 65yrs with HbA1c =7 and above and controls included 91 individuals 65yrs and above with HbA1c <7. Both groups were assessed for cognitive decline using MMSE score and CFS score determined their dependency status. Results: Moderately uncontrolled Diabetes had highest association with severe cognitive decline(50%) p-value 0.000 and those who could not manage to do IADLS were severely dementic in our study( p-value 0.046). We also found DM to be associated with high frailty scores. Severely uncontrolled DM was associated with CFS of 5 meaning those who were dependent on others for instrumental activities of daily living. Those who managed well independently was associated with Pre DM in our study.( p-value 0.041) Conclusion: Severe cognitive decline has high association with uncontrolled glycemic control. Keywords: IADLS (instrumental activities of daily living), CFS (chronic frailty scale), MCI (Mild Cognitive Impairment)